Dual-Energy CT Follow-Up After Stroke Thrombolysis Alters Assessment of Hemorrhagic Complications - Almqvist, Håkan; Almqvist, Niklas S.; Holmin, Staffan; Mazya, Michael V. (Frontiers in Neurology, 2020)
Background and Purpose: We aimed to determine whether dual energy CT (DECT) follow-up can differentiate contrast staining (CS) from intracranial hemorrhage (ICH) in stroke patients treated with intravenous thrombolysis (IVT), who had undergone acute stroke imaging using CTA and CTP. Materials and Methods: Between November 2012 and January 2018, 168 patients at our comprehensive stroke center underwent dual energy CT follow-up within 36 hours after IVT and acute CTA with or without CTP, but did not receive intraarterial imaging or treatment. Two independent readers evaluated plain monochromatic CT (pCT) alone, and compared this with a second reading of a combined DECT approach using pCT, water- and iodine-weighted images, establishing and grading the ICH diagnosis, per Heidelberg and SITS-MOST classifications. Results: On pCT alone within 36 hours, 31/168 (18.5 %) patients had findings diagnosed as ICH. Using cDECT changed ICH diagnosis to “contrast staining only” in 3/168 (1.8 %), patients, constituting 3/31 (9.7 %) of cases with initially pCT-diagnosed ICH. These three cases had pCT diagnoses of one SAH, one minor, and one more extensive petechial hemorrhage (hemorrhagic infarction type 1 and 2) respectively. pCT alone had a 100 % sensitivity, 98 % specificity, 90 % PPV, 100 % NPV, and 98 % accuracy for any ICH, compared to the combined DECT. Inter-reader agreement for ICH classification using pCT compared to DECT was weighted kappa 0.92 (95 % CI 0.87-0.98) versus 0.91 (0.85-0.95). Conclusion: Compared to plain CT, DECT within 36 hours after IV thrombolysis for acute ischemic stroke, changes the radiological diagnosis of post-treatment ICH to “contrast staining only” in a small proportion of patients. Studies are warranted of whether the altered radiological reports have an impact on patient management, for example initiation timing of antithrombotic secondary prevention.